P–172 Data-independent acquisition-proteomics of human embryo-spent medium and identification of potential embryo biomarkers. (6th August 2021) - Pathak, M; Venkatappa, V; Vasan, S S; Prasad, K; Narayana, C; Adiga, S; Varsha, S R; Sachdeva, G; Seshagiri, P B
Abstract: Study question: Can human embryo-derived protein(s) serve as viability biomarkers to predict pregnancy outcome, post embryo transfer? Summary answer: The human embryo-spent medium proteome, using data-independent acquisition (DIA) approach, could identify novel biomarkers for use in elective embryo transfer. What is known already: Morphological assessment is used for elective embryo transfer. To improve IVF outcomes and to avoid multiple gestations, embryo-viability assessment is required toward single embryo transfer. Embryo proteomics could provide a non-invasive approach to assess embryo viability. With the advent of DIA mode proteomics, a robust proteome of E-SM could be determined. Study design, size, duration: This was a retrospective study performed between May and December, 2020 using ten E-SMs obtained from ten individual transferable-quality embryos. Frozen E-SMs, following post-thaw, were subjected to LC-MS-MS analysis. Identified proteome profiles were being potentially correlated to embryo quality scores and pregnancy outcomes in terms of live births. Participants/materials, setting, methods: The E-SMs were processed for proteomic analysis and subjected to reduction, alkylation and trypsin digestion. Trypsin digested samples were desalted followed by LC-MS/MS using DIA method. Obtained results were searched against human peptide spectral library using Skyline. Differentially expressed proteins were identified by MSStat. Individual peptide peak area under the curve was normalized and analyzed using Student t-test. Fold change was calculated to identify differentially regulated proteins in blank and E-SM samples. Main results and the role of chance: Using a high-resolution mass spectrometer and high throughput DIA method, we identified 5, 502 peptides corresponding to 3, 396 proteins from blank and E-SM samples, derived from five non-transferred embryos. We observed that 516 proteins were specific to E-SMs vies-a-vies those of embryo-free blank medium. Statistical analysis showed that 25 proteins were significantly present E-SMs vs. blank. Interestingly, we observed that 16 proteins were down regulated and 9 were up regulated in E-SMs vs. blank medium. Furthermore, E-SMs, from transferred embryos, contained 2, 467 peptides corresponding to 1, 741 proteins; of these, 1, 689 proteins were specific to E-SMs with 60 (58 down regulated and 2 up regulated) of them being significantly expressed in E-SMs vis-à-vis embryo-free blank medium. Considering the available met analysis published data, our study is the first to use DIA acquisition for high-throughput analysis of human embryo proteome and identification of biomarkers of embryo viability and for possible prediction of pregnancy outcome. Limitations, reasons for caution: Proteins, other than HAS, detected in the blank medium could be because of non-purified HAS or undeclared proteins and DIA approach used. A large cohort study and meta-analysis using DIA mode are required to establish the embryo-proteome having predictive potential for embryo biological viability. Wider implications of the findings: For the first time, using DIA mode, a global embryo proteome assessment could be made, establishing a novel embryo viability biomarkers. This, along with the morphological analysis, could be practiced for selection of transferable quality embryo(s) Trial registration number: Not applicable